2018
DOI: 10.5815/ijitcs.2018.07.01
|View full text |Cite
|
Sign up to set email alerts
|

SASMEDU: Security Assessment Method of Software in Engineering Education

Abstract: Security and usability of web and mobile applications where users share their personal information have become to be a factor about which users should be careful. Rapid increase of developers, programming at early ages, desire for earning money by working freelance have caused widespread use of web and mobile applications and an increase of codes which contain vulnerabilities. Safe and good software development is also based on software lessons given to the students in high school or college years. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The main activity of the enterprise in particular and within a more compound structure is modeled. The analysis of existing scientific literature in this field shows that modeling is mostly focused on either maximization of commercial revenues or minimization of expenses [10][11][12][13][14][15][16][17][18][19]. This time as manufacturing processes are mostly carried out with extensive methods, innovative processes, the application of innovations stay out of focus.…”
Section: About Formulation and Study Level Of The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The main activity of the enterprise in particular and within a more compound structure is modeled. The analysis of existing scientific literature in this field shows that modeling is mostly focused on either maximization of commercial revenues or minimization of expenses [10][11][12][13][14][15][16][17][18][19]. This time as manufacturing processes are mostly carried out with extensive methods, innovative processes, the application of innovations stay out of focus.…”
Section: About Formulation and Study Level Of The Problemmentioning
confidence: 99%
“…In general, the solution algorithm of MACROMOD and MICROMOD models system can be constructed as below. Initially, i F and i  form is determined [14][15][16][17][18][19][20].…”
Section: Conceptual Scheme Of Solution Algorithm Of Models Systemmentioning
confidence: 99%
“…By comparing with the training mode of engineering talents in developed countries such as Europe and America, it could be found that engineering education in our country has always given people the impression that it attaches importance to the classroom, neglects extracurricular activities, emphasizes theory and neglects practice [18,19]. Due to the lack of effective practical teaching and the disconnection between theory and practice, the theoretical knowledge of classroom teaching cannot be effectively consolidated and the practical problems faced by engineering cannot be solved effectively.…”
Section: Design Of Innovative Talents Training Mode Under the Background Of Eeementioning
confidence: 99%